Highly Reversible Sodium Metal Battery Anodes via Alloying Heterointerfaces. Issue 37 (11th August 2022) - Deng, Yue; Zheng, Jingxu; Zhao, Qing; Yin, Jiefu; Biswal, Prayag; Hibi, Yusuke; Jin, Shuo; Archer, Lynden A.
Abstract: As a promising pathway toward low‐cost, long‐duration energy storage, rechargeable sodium batteries are of increasing interest. Batteries that incorporate metallic sodium as anode promise a high theoretical specific capacity of 1166 mAh g −1, and low reduction potential of −2.71 V. The high reactivity and poor electrochemical reversibility of sodium anodes render sodium metal anode (SMA) cells among the most challenging for practical implementation. Here, the failure mechanisms of Na anodes are investigated and the authors report that loss of morphological control is not the fundamental cause of failure. Rather, it is the inherently poor anchoring/root structure of electrodeposited Na to the electrode substrate that leads to poor reversibility and cell failure. Poorly anchored Na deposits are prone to break away from the current collector, producing orphaning and poor anode utilization. Thin metallic coatings in a range of chemistries are proposed and evaluated as SMA substrates. Based on thermodynamic and ion transport considerations, such substrates undergo reversible alloying reactions with Na and are hypothesized to promote good root growth—regardless of the morphology. Among the various options, Au stands out for its ability to support long Na anode lifetime and high reversibility (Coulombic Efficiency > 98%), for coating thicknesses in the range of 10–1000 nm. As a first step toward evaluating practical utility of the anodes, their performance in Na||SPAN cells with N:P ratio close to 1:1 is evaluated. Abstract : Alloying metal coatings with moderate Na diffusivities and low thickness, which retain mechanical integrity during charge–discharge cycling, and improve reversibility of Na metal anodes by a root‐growth mechanism are presented here. The coatings anchor Na electrodeposits and limit orphaning. Among the various options, Au with thicknesses in the range 10–1000 nm stands out for enabling long Na anode lifetime in liquid electrolytes.